Synthesis of magnetic ionic liquids and teaching materials: practice in a science fair - Takagi Yumiko (Chemistry Teacher International)
Applications of magnetic ionic liquids have been receiving growing interest recently. The magnetic properties of magnetic ionic liquids have been included in high school science textbooks in Japan as an area of possible future development. In the Science Fair event described here, magnetic ionic liquids synthesized in various ratios were correlated with their thermodynamic properties. This article describes Microscale Chemistry for a science fair with a focus on elementary school students as the target audience. Magnetic ionic liquids can be expected to become a new class of materials with potential for further educational applications in a more sustainable way.